2020
DOI: 10.1016/j.jpsychires.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sequential theta burst stimulation for multiple-therapy-resistant depression: A naturalistic observation study

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Our results demonstrate 58.3% to 72.2% improvement in depressive symptoms in patients receiving biTBS after treatment and during follow‐ups. These are similar to or higher than results obtained by previous studies using biTBS protocols delivering 600 pulses to each site 7,10,28 . Plewnia et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results demonstrate 58.3% to 72.2% improvement in depressive symptoms in patients receiving biTBS after treatment and during follow‐ups. These are similar to or higher than results obtained by previous studies using biTBS protocols delivering 600 pulses to each site 7,10,28 . Plewnia et al .…”
Section: Discussionsupporting
confidence: 90%
“…(2014) had a 56% response rate after 20 sessions. Burhan et al 10 . had a 52% response rate in 50 patients with TRD after 20 sessions in a naturalistic setting.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The TMS Machine (Magstim ® Rapid 2, UK) was used to apply the paradigm published previously [ 16 ]. Briefly, 600 pulses of continuous TBS (cTBS) was applied to F4 location and subsequently iTBS to F3 location with burst frequency between 40 and 50 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to burst sequence, Plewnia et al [ 15 ] found that the bilateral TBS protocol, that we used, was safe and superior to sham stimulation for the treatment of major depression. Further, we recently reported good efficacy and tolerability for bilateral sequential theta-burst applications in TRD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%